2014
DOI: 10.1097/mib.0000000000000060
|View full text |Cite
|
Sign up to set email alerts
|

Birth Outcomes in Women with Inflammatory Bowel Disease

Abstract: Women with UC and CD are at increased risk of adverse birth outcomes, such as stillbirth, growth restriction, and preterm birth, particularly when they suffer from flares throughout pregnancy. Thiopurine exposure seems to further increase risks, independently of disease activity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
145
2
3

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 115 publications
(155 citation statements)
references
References 28 publications
5
145
2
3
Order By: Relevance
“…33 We found no absolute or relative increase in the risk of perinatal death, similar to the meta-analysis that found no difference in the rates of stillbirths in women with IBD, 33 which was different from the large Swedish study that found that women with CD had an increased risk of stillbirth. 11 This highlights the difficulty of comparing studies from different time periods and countries, as women may have had different disease management before or during pregnancy, which may explain the differences in outcomes.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…33 We found no absolute or relative increase in the risk of perinatal death, similar to the meta-analysis that found no difference in the rates of stillbirths in women with IBD, 33 which was different from the large Swedish study that found that women with CD had an increased risk of stillbirth. 11 This highlights the difficulty of comparing studies from different time periods and countries, as women may have had different disease management before or during pregnancy, which may explain the differences in outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…30 An association with increased disease activity in CD and preterm birth has previously been reported 31 as has an association between UC and preterm birth, and between CD and stillbirth and particularly when there were flares throughout pregnancy. 11 There is slight uncertainty regarding the inclusion of women with the first record of IBD diagnosis after birth in the study. There were 151 (5.4%) women with a first record of IBD in the 6 months after delivery.…”
Section: Strengths and Limitationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Adequate disease control is crucial to ensure the best fetal and maternal health, since high disease activity is associated with an increased risk of adverse pregnancy outcomes [9][10][11][12][13]. Anti-TNF agents provide an effective therapeutic option, however, they are often discontinued during the early stages of pregnancy to limit potential in utero exposure of the fetus and to reduce the risk of congenital malformations during organogenesis [14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…Preterm delivery and low birth weight was common in the CD cohort compared to pregnant women without CD. In a Swedish cohort of 1,220 births in women with CD, an increased risk of adverse birth outcomes, such as stillbirth, growth restriction, and preterm birth, were noted particularly in those who suffered from flares throughout pregnancy [142].…”
mentioning
confidence: 99%